FALL3D-8.0: a computational model for atmospheric transport and deposition of particles, aerosols and radionuclides – Part 1: Model physics and numerics - Folch, Arnau; Mingari, Leonardo; Gutierrez, Natalia; Hanzich, Mauricio; Macedonio, Giovanni; Costa, Antonio (Geoscientific Model Development, 2020)
This paper presents FALL3D-8.0, the last version release of an open-source code with 15+ years of track record and a growing number of users in the volcanological and atmospheric communities. The code has been redesigned and rewritten from scratch in the framework of the EU Centre of Excellence for Exascale in Solid Earth (ChEESE) in order to overcome legacy issues and allow for successive optimisations in the preparation of the code towards extreme-scale computing. However, this baseline version already contains substantial improvements in terms of model physics, solving algorithms, and code accuracy and performance. The code, originally conceived for atmospheric dispersal and deposition of tephra particles, has been extended to model other types of particles, aerosols and radionuclides. The solving strategy has also been changed, replacing the former central-difference scheme for a high-resolution central-upwind scheme derived from finite volumes, which minimises numerical diffusion even in the presence of sharp concentration gradients and discontinuities. The parallelisation strategy, input/output (I/O), model pre-process workflows and memory management have also been reconsidered, leading to substantial improvements on code scalability, efficiency and overall capability to handle much larger problems. All these new features and improvements have implications on operational model performance and allow, among others, adding data assimilation and ensemble forecast in future releases. This paper details the FALL3D-8.0 model physics and the numerical implementation of the code.